Reproductive indices in sows subjected to farrowing induction (Research, Society and Development, 2021)
Farrowing induction is a management approach adopted to improve farrowing assistance provided to matrices, as well as their reproduction rates. The aim of the current study is to investigate sodium Cloprostenol using to induce farrowing in swine matrices and its effect on their reproduction indices. Reproduction data of 76 sows were collected in the manager software of a Piglet Production Unit (PPU) in far west Paraná state. Treatments comprised Natural Farrowing – NF (without induction by exogenous hormone) and Induced Farrowing – IF (induced through Cloprostenol Sodium application) - both in daytime and nighttime periods. Farrowing induction has reduced the number of gestation days and the mean variation in the expected farrowing date; besides, it has concentrated 66% of farrowing cases at 115 gestation days. The IF group recorded shorter farrowing duration (in hours), as well as lower stillbirth and post- farrowing mortality rates. Total birth rate was also higher in the group subjected to IF. In addition, the induction procedure has concentrated 87.05% of farrowing cases at daytime. The group subjected to IF recorded live-born piglet rate 6.91% higher than NF. The use of labor inducers such as Cloprostenol Sodium was effective in concentrating farrowing cases at daytime, in increasing reproduction rates in swine matrices, as well as in decreasing variations in farrowing days, the number of gestation days and farrowing duration. All these factors made farrowing assistance easier.